Exploring the Linkage of Spatial Indicators from Remote Sensing Data with Survey Data: The Case of the Socio-Economic Panel (SOEP) and 3D City Models - Jan Goebel; Michael Wurm; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper demonstrates the spatial evaluation of survey data from the German Socio-Economic Panel (SOEP) study using geo-coordinates and spatially relevant indicators from remote sensing data. By geocoding the addresses of survey households with block-level geographic precision (while preventing their identification by name and guaranteeingtheir complete anonymity), data on SOEP respondents can now be analyzed in a specific spatial context. In the past, regional analyses of SOEP based on official regional indicators (e.g., the unemployment rate) always had only very imprecise spatial information to work with. This limitation has now been overcome with the geocoded respondents' information. Within a protected unit of the fieldwork organization responsible for SOEP (TNS Infratest, Munich), the addresses of survey households can now be used to generate a variable describing the location of the household with block-level precision. At DIW Berlin, this additional variable is fed into a special computer infrastructure with multiple security layers that makes the socio-economic analysis possible. This paper demonstrates the use of this geographicallocation and remote sensing data to check respondents' subjective assessments of the location of their residence, anddiscusses the analytical potential of linking remote sensing data and survey data.
Keywords: C81; C83; R14; 330; Remote sensing data; social sciences; behavioral sciences; multi-disciplinarity; SOEP; Panel; Privater Haushalt; Geoinformationssystem; Region; Satellitenkommunikation; Deutschland